The use of informed consent in dental practice in southern Peru - Quenaya Garay, Astridh Semiramis; Peñaloza De La Torre, Ulises Massino; Salazar Paco, Olga Elizabeth; Aldana Cáceres, Alejandro; Pezo Jiménez, Omar (Acta Bioethica, 2024)
The objective of this research is to determine how informed consent is used in dental practice in southern Peru in the year 2023. The methodological design adopts a descriptive level with a mixed approach that is divided into two stages: The first consisted of a qualitative theoretical-analytical-rational analysis, followed by a subsequent empirical analysis with a quantitative, descriptive and cross-sectional approach. The study was carried out in a population of dentists who practice the dental profession in southern Peru in the year 2023 with a non-probabilistic convenience sample of 131 dentists. The main results were that the use of informed consent (14.5%) states that they do not use it in their daily consultation and (59.5%) use it in an erroneous way, due to different factors that influence this procedure and that the non-use of informed consent in its highest percentage arguing "lack of time" on the part of dentists It was concluded that there is a high rate of dental professionals who do not use informed consent in their professional practice, even more so that there is a high percentage that does not use consent correctly reported as an ethical-legal document.